Integration reports: an analysis from the social services perspective - Nicolás Lizama, Mercedes (Cuadernos de Trabajo Social, 2018)
Administrative irregularities represent one of the greatest risk factors for immigrants in terms of social exclusion and marginalization, due to both the situation in itself and all the consequences it entails at the personal, cultural and social levels. The possibility of regularizing their situation due to exceptional circumstances such as integration enables the commencement of social integration processes. The latest regulatory amendments transfer greater power to autonomous communities and city councils with regard to administrative regularization processes. It is within this framework that social services and social work professionals have seen their duties increased, with the obligation to issue social integration reports. These new functions are not exempt from debate. Transfers of social control duties are closer to the approach of an assimilation model; proven ineffective in previous eras, this delegates the effort of integration mainly to the immigrant population and is shown to be harmful to intercultural co-existence.